1-Pyrene-butyrylcholine: a fluorescent probe for the cholinergic system. - Barrantes, F J (1975)
The action of 1-pyrene-butyrylcholine, a new cholinergic fluorescent probe, has been studied at the cellular level using electrophysiological and fluorescence techniques. The spectroscopic properties of the probe were found to be similar to those pf pyrene-butyric acid, the excited-state lifetime in air-saturated aqueous solutions being 92 nsec. At micromolar concentrations the probe was found to exert a nondepolarizing, reversible blocking action at the neuromuscular junction of the frog. The same cholinolytic effect was observed in hypersensitive denervated muscles. The synaptic localization of the probe could be observed with fluorescence microscopy using sub- and micromolar concentrations. Treatment of the nerve-muscle preparations with proteolytic enzymes, resulting in the separation of the nerve ending from the muscle end-plate, enabled a distinction to be made between the fluorescence arising from these two parts of the synapse. Intense presynaptic fluorescence was observed, and was not altered by micromolar concentrations of alpha-bungarotoxin, d-tubocurarine, hemicholinium, or cholinesterase inhibitors. Faint reversible staining of the end-plate region was observed in enzymically treated muscles and was inhibited by prior treatment with alpha-bungarotoxin. Fluorescent alpha-toxin revealed similar patterns of fluorescence in the end-plate of enzyme-treated muscles. The postsynaptic localization of the fluorescent probe is therefore tentatively identified as the one producing the cholinolytic effect upon binding to acetylcholine receptor sites.